Recombinant DNA : A Short Course - Watson, James D Caudy, Amy A (W.H. Freeman, 2007)
This text presents an introduction to the concepts and techniques of recombinant DNA research and their dramatic results. It explores core concepts in molecular biology in a contemporary inquiry-based context, building its coverage around the landmark experiments that redefined our understanding of DNA.